2017
DOI: 10.1080/24701394.2017.1320994
|View full text |Cite
|
Sign up to set email alerts
|

First molecular evidence of Mus musculus bactrianus in Nepal inferred from the mitochondrial DNA cytochrome B gene sequences

Abstract: To identify the house mice collected in Pokhara and Lumbini of Nepal at the subspecies level, morphological and molecular analyses were carried out. Morphologically, two populations collected in Pokhara and Lumbini were distinguished by fur colour, but there was no significant difference in external measurements (p > .05). The phylogenetic analysis results revealed that the haplotypes sequences of mitochondrial DNA (mtDNA) Cytochrome B (CytB) gene distinguished into two distinct clades on a phylogenetic tree r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
1
12
3
Order By: Relevance
“…However, our study did not genotype R. rattus and Mus musculus mice. Nevertheless, earlier studies reported the presence of both R. norvegicus and M. musculus doemesticus from Bangladesh (Adhikari et al 2018 ; Barman et al 2020 ). The prevalence of RVA in our studied rodents was higher than in previous studies (Li et al 2016 ; Ianiro et al 2017 ), but in the case of shrews, our results are similar to those of a former study from China that found a 6.7% seroprevalence in wild tree shrews ( Tupaia belangeri Chinese) using antigen-capture ELISA (Wang et al 2011 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, our study did not genotype R. rattus and Mus musculus mice. Nevertheless, earlier studies reported the presence of both R. norvegicus and M. musculus doemesticus from Bangladesh (Adhikari et al 2018 ; Barman et al 2020 ). The prevalence of RVA in our studied rodents was higher than in previous studies (Li et al 2016 ; Ianiro et al 2017 ), but in the case of shrews, our results are similar to those of a former study from China that found a 6.7% seroprevalence in wild tree shrews ( Tupaia belangeri Chinese) using antigen-capture ELISA (Wang et al 2011 ).…”
Section: Discussionmentioning
confidence: 97%
“…MtDNA CytB was amplified using primers L14724 and H15915 designed by Irwin et al (1991). Polymerase chain reactions (PCRs) were performed according to the procedure of Adhikari et al (2017). The purified PCR products amplified were directly sequenced with a DNA sequencing ABI 3130XL Genetic Analyzer (Applied Biosystems, Foster, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Beyond these three primary subspecies, a number of secondary house mouse subspecies have also been suggested on the basis of distinct morphology 8–10 and surveys of limited numbers of molecular markers 5,1015 . For example, mice from Yemen and Madagascar have been assigned to M. m. gentilulus due to their small size and distinct mitochondrial lineage 11,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Mice from Heligoland, a small German archipelago island in the North Sea, have been characterized as M. m. helgolandicus due to their unique skull morphology, distinct mitochondrial D-loop haplotype, and allelic variation at four nuclear loci 10,16 . Similarly, mitochondrial sequence analysis has been used to assign house mice from Pakistan to the subspecies M. m. bactrianus 15,17 . M. m. musculus and M. m. castaneus naturally hybridize where their ranges overlap in Japan, and these hybrids have been designated as a distinct subspecies, M. m. molossinus 18 .…”
Section: Introductionmentioning
confidence: 99%